Overexpression of a NF-YC Gene Results in Enhanced Drought and Salt Tolerance in Transgenic Seashore Paspalum - Wu, Xueli; Shi, Haifan; Guo, Zhenfei (Frontiers in Plant Science, 2018)
Seashore paspalum (Paspalum vaginatum O. Swartz) is an important warm-season turfgrass species. In this study we generated transgenic seashore paspalum overexpressing CdtNF-YC1, a nuclear factor Y transcription factor from hybrid bermudagrass (Cynodon dactylon × Cynodon transvaalensis). DNA blot hybridization and qRT-PCR analysis showed that CdtNF-YC1 was integrated into the genomes of transgenic seashore paspalum plants and expressed. Reduced relative water content (RWC) and survival rate and increased ion leakage were observed in both wild type and transgenic plants after drought stress, while transgenic plants had higher levels of RWC and survival rate and lower ion leakage than the wild type (WT). Maximal photochemical efficiency of photosystem II (Fv/Fm), chlorophyll concentration and survival rate were decreased after salt stress, while higher levels were maintained in transgenic plants than in WT. In addition, an increased Na+ content and decreased or unaltered K+ in leaves and roots were observed after salt treatment, while lower level of Na+ and higher levels of K+ and K+/ Na+ ratio were maintained in transgenic plants than in WT. The results indicated that overexpressing CdtNF-YC1 resulted in enhanced drought and salt tolerance in transgenic plants. Transcript levels of stress responsive genes including PvLEA3, PvP5CS1, PvABI2 and PvDREB1B were induced in response to drought and salt stress, and higher levels were observed in transgenic seashore paspalum than in WT. The results suggest that the enhanced drought and salt tolerance in transgenic seashore paspalum is associated with induction of a series of stress responsive genes as a result of overexpression of CdtNF-YC1.